Projetos e simulações de protótipos virtuais para máquinas recolhedora de caju - Paulo, Marcos Antônio de Lemos (2014)
Using CAD software and CAE, engineers and designers can simulate the dynamic and static mechanical components, including effects of friction and mass, cycle times and performance of individual components before specifying a single physical piece and connect it to machinery, equipment or actual control algorithm. A virtual prototype provides the ability to view and optimize a design and evaluate different concepts and studies before submitting to the cost of physical prototypes. This study aimed to demonstrate the importance of CAD / CAE systems to increase the degree of reliability and safety with respect to the validation and / or performance improvement of mechanical industrial projects, agricultural machinery and equipment. For this, the techniques practiced by the industries for such purposes, is being touted as possible to anticipate potential failures in these projects quickly and cost through the use of CAD / CAE systems were investigated. Also, were pointed out the advantages of CAD / CAE systems compared to other tools presented previously practiced by industries for validation and / or improvement of performance in industrial projects. By using the software of CAD / CAE parts, manual and semiautomatic machines were designed to make the recolheita cashew.